A functional current collector based on gradient porous structure and a preparation method thereof
Patent Information
- Application Number
- CN202611002543.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-27
AI Technical Summary
当前行业主流趋势是采用4~5μm超薄基膜(如PET、改性PP)进一步提升电池能量密度,但超薄基膜的电镀铜过程面临两大核心痛点:(1)界面结合力与力学强度失衡:超薄基膜力学承载能力弱,传统单一孔隙刻蚀易导致基膜断裂,而无孔隙处理则使铜镀层附着力不足(ASTMD3359划格测试多为3B级),无法满足电池循环过程中的弯折需求;(2)镀层均匀性与工艺适配性差:1μm超薄铜镀层对沉积工艺敏感性高,传统直流电镀易出现浓差极化,导致镀层厚度偏差超±10%,且无法充分填充基膜表面孔隙,浪费锚定潜力
1、本发明中通过“图案化异质结”与“梯度孔隙”的协同作用,不仅能调控电场分布,实现锂离子均匀沉积,提升电池循环稳定性,还能与梯度孔隙形成协同锚定结构,提高镀铜层的附着力,提高高分子基膜的拉伸强度。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of current collector technology, specifically a functional current collector based on a gradient pore structure and its preparation method. Background Technology
[0002] Composite current collectors, due to their sandwich structure of "polymer base film + metal coating", have advantages in lightweight, high safety and low cost, and have become the core direction to replace traditional electrolytic copper foil. The current mainstream trend in the industry is to use 4~5μm ultrathin base film (such as PET, modified PP) to further improve the energy density of batteries. However, the copper plating process of ultrathin base film faces two major pain points: (1) Imbalance between interfacial bonding force and mechanical strength: The mechanical bearing capacity of ultrathin base film is weak. Traditional single-pore etching is prone to causing the base film to break. Poreless treatment results in insufficient adhesion of copper coating (ASTM D3359 cross-cut test is mostly 3B grade), which cannot meet the bending requirements during battery cycling; (2) Poor coating uniformity and process adaptability: 1μm ultrathin copper coating is highly sensitive to deposition process. Traditional DC electroplating is prone to concentration polarization, resulting in coating thickness deviation of more than ±10%, and it cannot fully fill the pores on the surface of the base film, wasting anchoring potential. Pore structure design lacks specificity: Existing technologies focus on controlling porosity alone, without forming a coordinated design of the thickness ratio of the "surface layer-inner layer-coating layer", resulting in either insufficient electrolyte wetting or mechanical failure of the base film (tensile strength below 600MPa).
[0003] In the prior art, CN118292060A discloses the use of copper sulfate, sulfuric acid, and lanthanum salt (lanthanum nitrate) in pulse electroplating solution, CN115725927A mentions rare earth lanthanum combined with dual-pulse process, polyethylene glycol as a conventional copper plating additive has been disclosed in CN107177868A, and PET argon plasma etching is also a conventional technology. The existing technologies have not solved the technical gaps in the synergistic matching of gradient porosity of ultrathin base film and coating, balance between electrolyte stability and coating crystallization consistency, and control of the lithium affinity of base film surface, and cannot meet the long-term cycle requirements of high-rate batteries.
[0004] To address the technical bottleneck of copper electroplating on 4-5μm ultrathin base films, this invention provides a method for preparing a functional current collector based on a gradient pore structure. Through a structural design of "surface high-porosity anchoring - inner layer transition buffer - bulk mechanical support," combined with a dual-pulse electroplating process, it adds three innovative technical points: "modified polyether synergistic additive system," "patterned heterojunction pretreatment," and "gradual control of current density." This achieves a performance balance of "adhesion ≥ 4B grade, tensile strength ≥ 700MPa, and coating deviation ≤ ±3.5%," while simultaneously improving electrolyte utilization to over 92%, thus overcoming the technical deficiencies of existing technologies. Summary of the Invention
[0005] The purpose of this invention is to provide a functional current collector based on a gradient pore structure and its preparation method, so as to solve the problems raised in the prior art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a functional current collector based on a gradient pore structure, comprising the following processes: Step 1: Take a polymer base film, clean it, dry it and perform mask plasma etching to form a lithiophilic patterned heterojunction array on its surface, and then perform low-damage plasma etching to form a gradient pore structure, thus obtaining a pretreated polymer base film with a composite structure. Step 2: Mix copper sulfate, sulfuric acid, lanthanum nitrate, polyethylene glycol, modified polyether and deionized water, stir at 30~35℃ for 25~30 min, let stand for 22~24 h to obtain electroplating solution; Step 3: Take the pretreated polymer base film, put it into the electroplating solution, and electroplat it to form an electroplated copper layer. After the electroplating is completed, rinse and dry it to obtain the functional current collector.
[0007] Furthermore, in step 1, the cleaning is performed using anhydrous ethanol for ultrasonic cleaning, with the specific process conditions being: power 90~100W, time 4~5min; The drying process conditions are: temperature 55~60℃, time 25~30min.
[0008] Furthermore, in step 1, the polymer base film is one of PET base film and modified PP base film; The thickness of the polymer base film is 4~5μm.
[0009] Furthermore, in step 1, the process conditions for plasma etching of the mask are as follows: zinc oxide is used as the heterojunction material, the etched pattern is circular with a diameter of 5~8μm, and the pattern spacing is 2.5~6.4μm.
[0010] Furthermore, in step 1, the ratio of the array area of the plasma etching of the mask to the surface area of the polymer base film is (0.6~0.8):1.
[0011] Furthermore, in step 1, the spacing between adjacent heterojunctions in the lithiophilic patterned heterojunction array is 0.5 to 0.8 times the lateral dimension of the etched pattern.
[0012] Furthermore, in step 1, when the polymer base film is a PET base film, argon gas is used for plasma low-damage etching. The specific process conditions are: power 180~220W, time 25~30s, and argon gas flow rate 15~20sccm. The thickness of the surface void layer formed after etching is 0.4~0.6μm, and the porosity of the surface void layer is 40~50%. The thickness of the inner void layer formed after etching is 0.6~1.38μm, and the porosity of the inner void layer is 15~22%. The thickness of the etched PET base film is ≥2.8μm.
[0013] Furthermore, in step 1, when the polymer base film is a modified PP base film, a mixed gas of oxygen and argon at a volume ratio of 1:3 is used for plasma low-damage etching. The specific process conditions are: power 200~240W, time 30~35s, and mixed gas flow rate 18~25sccm. The thickness of the surface void layer formed after etching is 0.5~0.7μm, and the porosity of the surface void layer is 40~45%. The thickness of the inner void layer formed after etching is 0.75~1.61μm, and the porosity of the inner void layer is 15~20%. The thickness of the modified PP base film after etching is ≥2.7μm.
[0014] Furthermore, in step 1, the ratio x of the thickness of the etched polymer base film to the thickness of the unetched polymer base film satisfies the following relationship: 0.6 ≤ x < 1.
[0015] Furthermore, in step 2, the electroplating solution comprises the following components by mass: copper sulfate 180~220g / L, sulfuric acid 45~55g / L, lanthanum nitrate 0.02~0.05g / L, polyethylene glycol 0.2~0.4g / L, and modified polyether 0.1~0.3g / L.
[0016] Furthermore, in step 2, the modified polyether is obtained by mixing polyether sulfonate and polyether compound at a mass ratio of 1:2; The polyether sulfonate is sodium fatty acid methyl ester polyether sulfonate; The polyether compound is sodium nonylphenol polyoxyethylene ether sulfate.
[0017] Furthermore, the pH value of the electroplating solution is 1 to 2.
[0018] Furthermore, in step 3, a dual-pulse power supply is used for electroplating, with the pretreated polymer base film as the cathode and the titanium mesh as the anode, and the distance between the two electrodes is 4~6cm.
[0019] Furthermore, in step 3, the current density is controlled in stages during electroplating, and the specific process is as follows: when the polymer base film is a PET base film; The initial process conditions for electroplating are: forward current density 1.2~1.5A / dm³. 2 Pulse width 35~40ms; reverse current density 0.3~0.4A / dm³ 2 Pulse width 3~5ms, electroplating time 4~5min; The process conditions during the intermediate stage of electroplating are: forward current density 1.8~2.2 A / dm³. 2 Pulse width 30~35ms; reverse current density 0.4~0.6A / dm³ 2 Pulse width 2~4ms, electroplating time 7~8min; The post-electroplating process conditions are: forward current density 1.5~1.8 A / dm³. 2 Pulse width 25~30ms; reverse current density 0.3~0.4A / dm³ 2 Pulse width 3~5ms, electroplating time 4~5min; The electroplating process has a duty cycle of 50-60%, an electroplating temperature of 40-42℃, a total electroplating time of 15-18 min, and a copper layer thickness of 0.56-1.5 μm. When the polymer base film is a modified PP base film; The initial process conditions for electroplating are: forward current density 1.5~1.8 A / dm³. 2 Pulse width 40~45ms; reverse current density 0.4~0.5A / dm³ 2 Pulse width 4~6ms, electroplating time 5~6min; The process conditions during the intermediate stage of electroplating are: forward current density 2.0~2.4A / dm³. 2 Pulse width 30~35ms; reverse current density 0.5~0.7A / dm³ 2 Pulse width 2~4ms, electroplating time 7~8min; The post-electroplating process conditions are: forward current density 1.8~2.0 A / dm³. 2 Pulse width 25~30ms; reverse current density 0.4~0.5A / dm³ 2 Pulse width 4~6ms, electroplating time 6~7min; The electroplating process has a duty cycle of 45-55%, an electroplating temperature of 38-40℃, a total electroplating time of 18-21 min, and a copper layer thickness of 0.7-1.75 μm.
[0020] Furthermore, the thickness ratio of the surface void layer, the inner void layer, and the electroplated copper layer of the polymer base film is 1:(1.5~2.3):(1.4~2.5).
[0021] Furthermore, in step 3, during the electroplating process, the electrolyte is circulated in a closed loop through a ceramic membrane circulation filtration system. The specific process conditions are: filtration accuracy of 0.3~0.8μm and circulation flow rate of 8~12L / min.
[0022] Furthermore, in step 3, deionized water is used for rinsing, and the rinsing pressure is 0.1~0.2MPa; In step 3, the drying process conditions are: temperature 45~50℃, time 15~20min.
[0023] In the above technical solution, a lithiophilic semiconductor material (zinc oxide) is first used as the heterojunction material. A lithiophilic patterned heterojunction array is etched on the polymer base film to control the electric field distribution, achieve uniform lithium ion deposition, and improve the battery cycle stability. Then, plasma low-damage etching is performed to form a gradient pore structure, forming a composite surface structure of "patterned heterojunction + gradient pores". The total thickness of the gradient pore structure is ensured to be less than 40% of the thickness of the unetched polymer base film. The patterned heterojunction array is embedded in the surface void layer and forms a cooperative anchoring structure with the pores. The modified polyether added to the electrolyte works synergistically with lanthanum nitrate and polyethylene glycol. On the one hand, it improves the stability of the plating solution, maintaining compositional uniformity without the need for CVS (cyclic voltammetric stripping) testing, thus reducing production costs. On the other hand, it refines the coating grains, improves coating smoothness, and solves the defect of uneven crystallization in existing single additive systems. It also enhances the interfacial adhesion between the coating and the base film. Compared with the existing single lanthanum salt + polyethylene glycol additive system, it has a better copper plating effect. During electroplating, current density is controlled in stages. In the initial stage of electroplating, a low current density is used to avoid breakdown of the ultra-thin base film, while allowing copper ions to nucleate uniformly in the patterned heterojunction and gradient pores. In the middle stage of electroplating, a high current density is used to improve deposition efficiency, and modified polyether additives are used to refine the grains. In the later stage of electroplating, a low current density is used to smooth the coating surface and reduce roughness, solving the problems of excessively thick coating edges and incomplete pore filling caused by existing fixed current densities, thus comprehensively improving the quality of the electroplated copper layer.
[0024] Furthermore, the modified PP base film is prepared by the following process: PP resin, maleic anhydride-grafted PP, nano-SiO2, and antioxidant are mixed, melt-extruded through a twin-screw extruder, and cast to obtain a modified PP base film.
[0025] Furthermore, the mass ratio of PP resin, maleic anhydride-grafted PP, nano-SiO2, and antioxidant is (90~94):(3~5):(2~4):(0.2~0.5).
[0026] Furthermore, the process conditions for melt extrusion are: extrusion temperature 180~200℃, screw speed 180~220r / min.
[0027] Furthermore, the process conditions for tape casting are: casting temperature 120~140℃, cooling roller temperature 40~50℃.
[0028] Furthermore, the antioxidant is antioxidant 1010.
[0029] Furthermore, the thickness of the modified PP base film is 4~5μm.
[0030] Furthermore, the modified PP base film can also be prepared by the following process: S1: Mix 3-buten-1-ol, N,N-dimethylcyclohexylamine, and 1,4-dioxane, stir until homogeneous, then add 4-(2-epoxyethylene methoxy)benzoic acid. Under a nitrogen atmosphere, heat the mixture to react. After the reaction is complete, cool to 20-25°C, add NaOH, and stir at 90-100 r / min for 20-30 min. Filter the mixture and distill the filtrate to obtain a compound containing double bonds. S2: Mix polypropylene and xylene, heat to 110~120℃ under nitrogen atmosphere, stir evenly, cool to 75~85℃, then add benzoyl peroxide and compounds containing double bonds, react at constant temperature, add acetone after the reaction is complete, stir at 90~100r / min for 30~40min, cool, filter to obtain filter cake, which is high temperature resistant polypropylene; S3: Under nitrogen atmosphere protection, high-temperature resistant polypropylene and xylene are mixed, heated to 60~80℃, stirred evenly, then octadecanoyl chloride and triethylamine are added, and the reaction is carried out at a constant temperature. After the reaction is completed, the mixture is cooled, filtered, dried and ground to obtain modified polypropylene. S4: Modified polypropylene is melt-extruded, stretched into a film, and annealed to obtain a modified PP base film.
[0031] Furthermore, in S1, the molar ratio of 3-buten-1-ol, N,N-dimethylcyclohexylamine, 1,4-dioxane, 4-(2-epoxyethylene methoxy)benzoic acid to NaOH is (1.0~1.5):(0.03~0.05):(20~35):1:(0.6~0.8).
[0032] Furthermore, in S1, the process conditions for the heating reaction are: temperature 90~100℃, time 5~7h; In S1, the distillation process conditions are: temperature 50~60℃, time 30~35min.
[0033] Furthermore, in S2, the mass ratio of polypropylene, xylene, benzoyl peroxide, double-bonded compound and acetone is (70~90):(100~150):(0.4~0.6):(8~10):(100~150).
[0034] Furthermore, in S2, the process conditions for the isothermal reaction are: temperature 75~85℃, time 1.5~2.0h.
[0035] Furthermore, in S3, the mass ratio of high-temperature resistant polypropylene, xylene, octadecyl chloride and triethylamine is (8~10):(50~70):(0.8~1.0):(0.3~0.5).
[0036] Furthermore, in S3, the process conditions for the isothermal reaction are: temperature 60~80℃, time 2~3h.
[0037] In S3, the drying process conditions are: temperature 50~60℃, time 4~6h.
[0038] Furthermore, in S4, the melt extrusion temperature is 240~250℃; In S4, the annealing process conditions are: temperature 110~120℃, time 60~70min.
[0039] In the above technical solution, firstly, the hydroxyl groups of 3-buten-1-ol react with the epoxy groups of 4-(2-epoxyethylene methoxy)benzoic acid to generate hydroxyl groups while retaining the double bonds, thus obtaining a compound containing double bonds. Then, under the action of benzoyl peroxide, the compound containing double bonds undergoes free radical addition with polypropylene, introducing benzoic acid groups with high-temperature resistance into the polypropylene molecular chain to obtain high-temperature resistant polypropylene. Through nucleophilic substitution of the hydroxyl groups on the high-temperature resistant polypropylene molecular chain with octadecanoyl chloride, long carbon chain flexible segments are introduced to enhance the mechanical properties of polypropylene, thus obtaining modified polypropylene. Finally, the modified polypropylene is melt-extruded into a film to obtain a modified PP base film.
[0040] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, the synergistic effect of "patterned heterojunction" and "gradient pores" can not only regulate the electric field distribution and achieve uniform lithium ion deposition to improve battery cycle stability, but also form a synergistic anchoring structure with gradient pores to improve the adhesion of copper plating layer and improve the tensile strength of polymer base film.
[0041] 2. The modified polyether introduced into the copper plating solution of the present invention forms a synergistic effect with lanthanum nitrate and polyethylene glycol, which can maintain the stability of the plating solution without the need for CVS testing, thereby reducing production costs. At the same time, it refines the coating grains and improves the coating smoothness, so that the coating thickness deviation is controlled within ±2.8%-±3.5%, which is far superior to the coating quality of existing single additive systems, and solves the defects of poor plating solution stability and uneven coating crystallization in existing technologies.
[0042] 3. This invention employs a current density gradient control process, which differs from the existing pulse process with a fixed current density. The gradient-controlled current density avoids the breakdown of the ultrathin base film and simultaneously achieves segmented control of "nucleation-deposition-smoothing," resulting in a continuous, pore-free coating with a pore filling rate of over 98%. This solves the problems of excessively thick coating edges and incomplete pore filling in existing processes. Furthermore, the use of low-damage plasma etching avoids base film breakdown, and the ceramic film circulation system increases electrolyte utilization to 92%~94.2%, reducing waste liquid emissions by over 50% compared to traditional processes. It is compatible with high-power magnetron sputtering continuous production equipment. The high-porosity surface layer (40%~50%) and patterned heterojunction work synergistically to increase the electrolyte wetting rate by 55%, achieving a capacity retention rate of 92% after 500 high-rate charge-discharge cycles. Simultaneously, the 1μm coating combined with the 4.5μm base film results in a total current collector thickness of ≤6.5μm, increasing battery energy density by 3.1%.
[0043] 4. In this invention, maleic anhydride grafted onto PP in the modified PP base film enhances the surface activity of PP, nano-silica strengthens the mechanical strength of the base film, and antioxidants prevent PP degradation during the molding process. The three work synergistically to solve the defects of low surface energy and insufficient mechanical strength of traditional modified PP base films, making them suitable for ultra-thin specifications and subsequent electroplating processes.
[0044] 5. In this invention, benzoic acid groups with good thermal stability are introduced into the polypropylene molecular chain to improve the thermal stability of polypropylene and reduce the high-temperature shrinkage rate. The introduced long carbon chain can effectively enhance the toughness of polypropylene and improve its puncture resistance. The annealing process can significantly reduce the thermal shrinkage of the polypropylene film, making it have a longer service life and better stability when used as a current collector, and further improving the various properties of the current collector. Detailed Implementation
[0045] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0046] In the following specific implementation, Polyethylene glycol, molecular weight 6000; The polyether sulfonate is sodium polyether sulfonate, which is a fatty acid methyl ester. The polyether compound is sodium nonylphenol polyoxyethylene ether sulfate; Polypropylene, grade K9010; Nano-sized SiO2, with a particle size of 7~20nm; The antioxidant is antioxidant 1010; Maleic anhydride grafted onto PP, grade TF12; PP base film with a thickness of 4.5μm.
[0047] Example 1: When the polymer base film is a PET base film, a method for preparing a functional current collector based on a gradient pore structure includes the following processes: Step 1: Take a 4.5μm thick PET base film, clean and dry it, use zinc oxide as the heterojunction material, and perform mask plasma etching to form a lithiophilic patterned heterojunction array on its surface. Then, perform low-damage plasma etching to form a gradient pore structure, obtaining a pretreated PET base film with a composite structure. Step 2: Mix copper sulfate, sulfuric acid, lanthanum nitrate, polyethylene glycol, modified polyether, and deionized water, stir at 35℃ for 25 min, and let stand for 22 h to obtain the electroplating solution. Step 3: Take the pretreated PET base film, immerse it in the electroplating solution, and perform electroplating. A copper plating layer is formed, and after electroplating, it is rinsed and dried to obtain a functional current collector. In step 1, the cleaning is performed using anhydrous ethanol for ultrasonic cleaning, with the specific process conditions being: power 90W, time 4min; the drying process conditions are: temperature 55℃, time 25min. In step 1, the etching pattern of the mask plasma etching is circular with a diameter of 6μm and a pattern spacing of 3.0μm. In step 1, the ratio of the array area of the mask plasma etching to the surface area of the PET base film is 0.7:1. In step 1, adjacent heterojunctions in the lithiophilic patterned heterojunction array... The spacing is 0.5 times the lateral dimension of the etched pattern; in step 1, argon gas is used for low-damage plasma etching, with the specific process conditions being: power 180W, time 25s, and argon flow rate 15sccm; the thickness of the surface void layer formed after etching is 0.5μm, and the porosity of the surface void layer is 45%; the thickness of the inner void layer formed after etching is 1.0μm, and the porosity of the inner void layer is 18%; the ratio of the surface void layer thickness to the inner void layer thickness is 1:2; the thickness of the PET base film after etching is 3.0μm; in step 2, the electroplating solution includes the following mass components. The electroplating solution consists of: 200 g / L copper sulfate, 50 g / L sulfuric acid, 0.03 g / L lanthanum nitrate, 0.3 g / L polyethylene glycol, and 0.2 g / L modified polyether. In step 2, the modified polyether is obtained by mixing polyether sulfonate and polyether compound at a mass ratio of 1:2. The pH of the electroplating solution is 1. In step 3, electroplating is performed using a dual-pulse power supply, with a pretreated PET substrate film as the cathode and a titanium mesh as the anode, with a 5 cm distance between the electrodes. In step 3, the current density is gradually controlled during electroplating, as follows: The initial electroplating conditions are: forward current density 1.2 A / dm³. 2 Pulse width 40ms; reverse current density 0.3A / dm³ 2 The pulse width was 5ms, and the electroplating time was 5min. The process conditions during the middle stage of electroplating were: forward current density 1.8 / dm³. 2Pulse width 35ms; reverse current density 0.4A / dm³ 2 The pulse width was 4ms, and the electroplating time was 8min. The post-electroplating process conditions were: forward current density 1.5A / dm³. 2 Pulse width 30ms; reverse current density 0.3A / dm³ 2 The pulse width is 5ms, the electroplating time is 5min; the duty cycle of the electroplating process is 50%, the electroplating temperature is 40℃, the total electroplating time is 18min, and the thickness of the electroplated copper layer is 1.0μm; the thickness ratio of the surface void layer, the inner void layer and the electroplated copper layer of the PET base film is 1:2.0:2.0; in step 3, during the electroplating process, the electrolyte is circulated in a closed loop through a ceramic membrane circulation filtration system, and the specific process conditions are: filtration accuracy of 0.5μm and circulation flow rate of 10L / min; in step 3, deionized water is used for rinsing, and the rinsing pressure is 0.1MPa; in step 3, the drying process conditions are: temperature 45℃ and time 15min.
[0048] Example 2: When the polymer base film is a modified PP base film, a method for preparing a functional current collector based on a gradient pore structure includes the following processes: (1) Preparation of modified PP base film: PP resin, maleic anhydride-grafted PP, nano-SiO2, and antioxidant were mixed in a mass ratio of 94:5:4:0.5, and then melt-extruded using a twin-screw extruder and cast to obtain a 5μm thick modified PP base film. The melt extrusion process conditions were: extrusion temperature 200℃, screw speed 220r / min; the casting process conditions were: casting temperature 140℃, cooling roller temperature 50℃. (2) Preparation of functional current collectors: Step 1: Take a 5μm thick modified PP base film, clean and dry it, use zinc oxide as the heterojunction material, and perform mask plasma etching to form a lithiophilic patterned heterojunction array on its surface. Then, perform low-damage plasma etching to form a gradient pore structure, obtaining a pretreated modified PP base film with a composite structure. Step 2: Mix copper sulfate, sulfuric acid, lanthanum nitrate, polyethylene glycol, modified polyether, and deionized water, stir at 35℃ for 30 min, and let stand for 24 h to obtain an electroplating solution. Step 3: Take the pretreated modified PP base film, immerse it in the electroplating solution, and perform electroplating to form an electroplated structure. A copper plating layer is formed, followed by rinsing and drying to obtain a functional current collector. In step 1, ultrasonic cleaning is performed using anhydrous ethanol under the following conditions: power 100W, time 5min. The drying conditions are: temperature 60℃, time 30min. In step 1, the etched pattern is circular with a diameter of 5μm and a pattern spacing of 2.5μm. In step 1, the ratio of the array area of the plasma etched mask to the surface area of the modified PP base film is 0.6:1. In step 1, the spacing between adjacent heterojunctions in the lithiophilic patterned heterojunction array is 0.8 times the lateral dimension of the etched pattern. In step 1, plasma low-damage etching is performed using a mixed gas of oxygen and argon at a volume ratio of 1:3. Specific process conditions are: power 200W, time 30s, mixed gas flow rate 20sccm. The thickness of the surface void layer after etching is 0.6μm, and the porosity of the surface void layer is 40%. The thickness of the inner void layer after etching is 1.2μm, and the porosity of the inner void layer is 15%. The thickness of the modified PP base film after etching is 2.7μm. The thickness ratio of the surface void layer to the inner void layer is 1:2. In step 2, the electroplating solution includes the following... Mass composition: copper sulfate 190g / L, sulfuric acid 45g / L, lanthanum nitrate 0.02g / L, polyethylene glycol 0.2g / L, modified polyether 0.15g / L; In step 2, the modified polyether is obtained by mixing polyether sulfonate and polyether compound at a mass ratio of 1:2; the pH value of the electroplating solution is 1; In step 3, electroplating is carried out using a dual-pulse power supply, with the pretreated modified PP base film as the cathode and a titanium mesh as the anode, and the distance between the two electrodes is 6cm; In step 3, the current density is controlled in stages during electroplating, and the specific process is as follows: The initial process conditions for electroplating are: forward current density 1.5A / dm³. 2 Pulse width 45ms; reverse current density 0.4A / dm³ 2 The pulse width was 6 ms, and the electroplating time was 6 min. The process conditions during the middle stage of electroplating were: forward current density 2.0 A / dm³. 2 Pulse width 35ms; reverse current density 0.5A / dm³ 2 The pulse width was 4ms, and the electroplating time was 8min. The post-electroplating process conditions were: forward current density 1.8A / dm³. 2Pulse width 30ms; reverse current density 0.4A / dm 2 The pulse width was 6ms, the electroplating time was 6min; the duty cycle of the electroplating process was 55%, the electroplating temperature was 38℃, the total electroplating time was 20min, and the thickness of the electroplated copper layer was 1.0μm; the thickness ratio of the surface void layer, the inner void layer and the electroplated copper layer of the modified PP base film was 1:2:1.67; in step 3, during the electroplating process, the electrolyte was circulated in a closed loop through a ceramic membrane circulation filtration system, and the specific process conditions were: filtration accuracy of 0.5μm and circulation flow rate of 10L / min; in step 3, deionized water was used for rinsing, and the rinsing pressure was 0.1MPa; in step 3, the drying process conditions were: temperature 45℃ and time 15min.
[0049] Example 3: When the polymer base film is a modified PP base film, a method for preparing a functional current collector based on a gradient pore structure includes the following processes: (1) Preparation of modified PP base film: S1: 3-Buten-1-ol, N,N-dimethylcyclohexylamine, and 1,4-dioxane were mixed and stirred until homogeneous. Then, 4-(2-epoxyethylene methoxy)benzoic acid was added. The mixture was heated under a nitrogen atmosphere. After the reaction was complete, it was cooled to 25°C, and NaOH was added. The mixture was stirred at 100 r / min for 30 min, filtered, and the filtrate was distilled to obtain a compound containing double bonds. S2: Polypropylene and xylene were mixed and heated to 120°C under a nitrogen atmosphere. The mixture was stirred until homogeneous, then cooled to 85°C. Benzoyl peroxide and a compound containing double bonds were added, and the reaction was carried out at a constant temperature. After the reaction was completed, acetone was added, and the mixture was stirred at 100 r / min for 40 min. After cooling, the filter cake was obtained, which is the high-temperature resistant polypropylene. S3: Under a nitrogen atmosphere, the high-temperature resistant polypropylene and xylene were mixed, heated to 80℃, stirred evenly, and then octadecanoyl chloride and triethylamine were added. The reaction was carried out at a constant temperature. After the reaction was completed, the mixture was cooled, filtered, dried, and ground to obtain modified polypropylene. S4: The modified polypropylene was melt-extruded, stretched into a film, and annealed to obtain modified P P-based film; In S1, the molar ratio of 3-buten-1-ol, N,N-dimethylcyclohexylamine, 1,4-dioxane, 4-(2-epoxyethylene methoxy)benzoic acid to NaOH is 1.5:0.05:35:1:0.8; In S1, the heating reaction conditions are: temperature 100℃, time 7h; In S1, the distillation conditions are: temperature 60℃, time 35min; In S2, the mass ratio of polypropylene, xylene, benzoyl peroxide, double-bonded compounds, and acetone is 90:150: 0.6:10:150; In S2, the isothermal reaction process conditions are: temperature 85℃, time 2.0h; In S3, the mass ratio of high-temperature resistant polypropylene, xylene, octadecyl chloride and triethylamine is 10:70:1.0:0.5; In S3, the isothermal reaction process conditions are: temperature 80℃, time 3h; In S3, the drying process conditions are: temperature 60℃, time 6h; In S4, the melt extrusion temperature is 250℃; In S4, the annealing process conditions are: temperature 120℃, time 70min; (2) Preparation of functional current collectors: Step 1: Take a 4.5μm thick modified PP base film, clean and dry it, use zinc oxide as the heterojunction material, and perform mask plasma etching to form a lithiophilic patterned heterojunction array on its surface. Then, perform low-damage plasma etching to form a gradient pore structure, obtaining a pretreated modified PP base film with a composite structure. Step 2: Mix copper sulfate, sulfuric acid, lanthanum nitrate, polyethylene glycol, modified polyether, and deionized water, stir at 35℃ for 30 min, and let stand for 24 h to obtain an electroplating solution. Step 3: Take the pretreated modified PP base film, immerse it in the electroplating solution, and perform electroplating to form... A copper plating layer is formed, followed by rinsing and drying to obtain a functional current collector. In step 1, ultrasonic cleaning is performed using anhydrous ethanol, with the specific process conditions being: power 100W, time 5min; the drying process conditions are: temperature 60℃, time 30min. In step 1, the etched pattern is circular with a diameter of 5μm and a pattern spacing of 2.5μm. In step 1, the ratio of the array area of the plasma etched mask to the surface area of the modified PP base film is 0.6:1. In step 1, the spacing between adjacent heterojunctions in the lithiophilic patterned heterojunction array is 0.8 times the lateral dimension of the etched pattern. In step 1, plasma low-damage etching is performed using a mixed gas of oxygen and argon at a volume ratio of 1:3. The specific process conditions are: power 200W, time 30s, and mixed gas flow rate 20sccm. The thickness of the surface void layer after etching is 0.6μm, and the porosity of the surface void layer is 40%. The thickness of the inner void layer after etching is 1.2μm, and the porosity of the inner void layer is 15%. The thickness of the modified PP base film after etching is 2.7μm. The thickness ratio of the surface void layer to the inner void layer is 1:2. In step 2, the electroplating solution includes the following... Mass composition: copper sulfate 190g / L, sulfuric acid 45g / L, lanthanum nitrate 0.02g / L, polyethylene glycol 0.2g / L, modified polyether 0.15g / L; In step 2, the modified polyether is obtained by mixing polyether sulfonate and polyether compound at a mass ratio of 1:2; the pH value of the electroplating solution is 1; In step 3, electroplating is carried out using a dual-pulse power supply, with the pretreated modified PP base film as the cathode and a titanium mesh as the anode, and the distance between the two electrodes is 6cm; In step 3, the current density is controlled in stages during electroplating, and the specific process is as follows: The initial process conditions for electroplating are: forward current density 1.5A / dm³. 2 Pulse width 45ms; reverse current density 0.4A / dm³ 2 The pulse width was 6 ms, and the electroplating time was 6 min. The process conditions during the middle stage of electroplating were: forward current density 2.0 A / dm³. 2 Pulse width 35ms; reverse current density 0.5A / dm³ 2 The pulse width was 4ms, and the electroplating time was 8min. The post-electroplating process conditions were: forward current density 1.8A / dm³. 2Pulse width 30ms; reverse current density 0.4A / dm 2 The pulse width was 6ms, the electroplating time was 6min; the duty cycle of the electroplating process was 55%, the electroplating temperature was 38℃, the total electroplating time was 20min, and the thickness of the electroplated copper layer was 1.0μm; the thickness ratio of the surface void layer, the inner void layer and the electroplated copper layer of the modified PP base film was 1:2:1.67; in step 3, during the electroplating process, the electrolyte was circulated in a closed loop through a ceramic membrane circulation filtration system, and the specific process conditions were: filtration accuracy of 0.5μm and circulation flow rate of 10L / min; in step 3, deionized water was used for rinsing, and the rinsing pressure was 0.1MPa; in step 3, the drying process conditions were: temperature 45℃ and time 15min.
[0050] Example 4: When the polymer base film is a PET base film, a method for preparing a functional current collector based on a gradient pore structure includes the following processes: Step 1: Take a 4.5μm thick PET base film, clean and dry it. Using zinc oxide as the heterojunction material, perform mask plasma etching to form a lithiophilic patterned heterojunction array on its surface. Then, perform low-damage plasma etching to form a gradient porosity structure, obtaining a pretreated PET base film with a composite structure. Step 2: Mix copper sulfate, sulfuric acid, lanthanum nitrate, polyethylene glycol, modified polyether, and deionized water. Stir at 35℃ for 30 min and let stand for 24 h to obtain the electroplating solution. Step 3: Take the pretreated PET base film and immerse it in the electroplating solution for... Electroplating is performed to form a copper layer. After electroplating, the surface is rinsed and dried to obtain a functional current collector. In step 1, ultrasonic cleaning is performed using anhydrous ethanol, with the specific process conditions being: power 100W, time 5min; the drying process conditions are: temperature 60℃, time 30min; the PET base film thickness is 5μm; in step 1, the plasma etching pattern on the mask is circular with a diameter of 8μm and a pattern spacing of 6.4μm; in step 1, the ratio of the array area of the plasma etching on the mask to the surface area of the PET base film is 0.8:1; in step 1, In the lithiophilic patterned heterojunction array, the spacing between adjacent heterojunctions is 0.8 times the lateral dimension of the etched pattern; in step 1, low-damage plasma etching is performed using argon gas, with the specific process conditions being: power 220W, time 30s, and argon flow rate 20sccm; the thickness of the surface void layer formed after etching is 0.6μm, and the porosity of the surface void layer is 50%; the thickness of the inner void layer formed after etching is 1.1μm, and the porosity of the inner void layer is 22%; the thickness of the PET base film after etching is 3.0μm; in step 2, the electroplating solution includes the following mass components: The electroplating solution contains 210 g / L copper sulfate, 55 g / L sulfuric acid, 0.05 g / L lanthanum nitrate, 0.4 g / L polyethylene glycol, and 0.3 g / L modified polyether. In step 2, the modified polyether is obtained by mixing polyether sulfonate and a polyether compound at a mass ratio of 1:2. The pH of the electroplating solution is 2. In step 3, electroplating is performed using a dual-pulse power supply, with a pretreated PET substrate film as the cathode and a titanium mesh as the anode, with a 6 cm distance between the electrodes. In step 3, the current density is gradually controlled during electroplating, specifically as follows: the initial electroplating conditions are: forward current density 1.5 A / dm³. 2 Pulse width 40ms; reverse current density 0.4A / dm³ 2 The pulse width was 5ms, and the electroplating time was 5min. The process conditions during the middle stage of electroplating were: forward current density 2.2A / dm³. 2 Pulse width 35ms; reverse current density 0.6A / dm³ 2 The pulse width was 4ms, and the electroplating time was 7min. The post-electroplating process conditions were: forward current density 1.8A / dm³. 2 Pulse width 30ms; reverse current density 0.4A / dm 2The pulse width was 5ms, the electroplating time was 4min; the duty cycle of the electroplating process was 60%, the electroplating temperature was 42℃, the total electroplating time was 16min, and the thickness of the electroplated copper layer was 1.0μm; the thickness ratio of the surface void layer, the inner void layer and the electroplated copper layer of the PET base film was 1:1.8:1.67; in step 3, during the electroplating process, the electrolyte was circulated in a closed loop through a ceramic membrane circulation filtration system, and the specific process conditions were: filtration accuracy of 0.8μm and circulation flow rate of 12L / min; in step 3, deionized water was used for rinsing, and the rinsing pressure was 0.2MPa; in step 3, the drying process conditions were: temperature 50℃ and time 20min.
[0051] Example 5: When the polymer base film is a PET base film, a method for preparing a functional current collector based on a gradient pore structure includes the following processes: Step 1: Take a 5μm thick PET base film, clean and dry it, use zinc oxide as the heterojunction material, and perform mask plasma etching to form a lithiophilic patterned heterojunction array on its surface. Then, perform low-damage plasma etching to form a gradient pore structure, obtaining a pretreated PET base film with a composite structure. Step 2: Mix copper sulfate, sulfuric acid, lanthanum nitrate, polyethylene glycol, modified polyether, and deionized water, stir at 33℃ for 28 min, and let stand for 23 h to obtain the electroplating solution. Step 3: Take the pretreated PET base film, immerse it in the electroplating solution, and proceed with... Electroplating is performed to form a copper layer. After electroplating, the material is rinsed and dried to obtain a functional current collector. In step 1, ultrasonic cleaning is performed using anhydrous ethanol, with the specific process conditions being: power 95W, time 4.5min; the drying process conditions are: temperature 58℃, time 28min. In step 1, the etched pattern of the plasma etching mask is circular with a diameter of 7μm and a pattern spacing of 4.0μm. In step 1, the ratio of the array area of the plasma etching mask to the surface area of the PET base film is 0.7:1. In step 1, the lithium-philic patterned... The spacing between adjacent heterojunctions in the heterojunction array is 0.6 times the lateral dimension of the etched pattern; in step 1, low-damage plasma etching is performed using argon gas, with the specific process conditions being: power 200W, time 28s, and argon flow rate 18sccm; the thickness of the surface void layer formed after etching is 0.5μm, and the porosity of the surface void layer is 45%; the thickness of the inner void layer formed after etching is 1.0μm, and the porosity of the inner void layer is 18%; the thickness of the PET base film after etching is 3.5μm; in step 2, the electroplating solution includes the following components by mass: copper sulfate. The electroplating solution contains 200 g / L sulfuric acid, 50 g / L lanthanum nitrate, 0.03 g / L polyethylene glycol, 0.3 g / L modified polyether, and 0.2 g / L modified polyether. In step 2, the modified polyether is obtained by mixing polyether sulfonate and polyether compound at a mass ratio of 1:2. The pH of the electroplating solution is 1. In step 3, a dual-pulse power supply is used for electroplating, with a pretreated PET base film as the cathode and a titanium mesh as the anode, with a 5 cm distance between the electrodes. In step 3, the current density is gradually controlled during electroplating, as follows: The initial electroplating conditions are: forward current density 1.3 A / dm³. 2 Pulse width 38ms; reverse current density 0.3A / dm³ 2 The pulse width was 4ms, and the electroplating time was 4min. The process conditions during the middle stage of electroplating were: forward current density 2.0A / dm³. 2 Pulse width 33ms; reverse current density 0.5A / dm³ 2 The pulse width was 3ms, and the electroplating time was 7 minutes. The post-electroplating process conditions were: forward current density 1.6A / dm³. 2 Pulse width 28ms; reverse current density 0.4A / dm³ 2The pulse width was 5ms, the electroplating time was 4min; the duty cycle of the electroplating process was 55%, the electroplating temperature was 41℃, the total electroplating time was 15min, and the thickness of the electroplated copper layer was 1.0μm; the thickness ratio of the surface void layer, the inner void layer and the electroplated copper layer of the PET base film was 1:2.0:2.0; in step 3, during the electroplating process, the electrolyte was circulated in a closed loop through a ceramic membrane circulation filtration system, and the specific process conditions were: filtration accuracy of 0.5μm and circulation flow rate of 10L / min; in step 3, deionized water was used for rinsing, and the rinsing pressure was 0.1MPa; in step 3, the drying process conditions were: temperature 48℃ and time 18min.
[0052] Example 6: When the polymer base film is a PET base film, a method for preparing a functional current collector based on a gradient pore structure includes the following processes: Step 1: Take a 4μm thick PET base film, clean and dry it, use zinc oxide as the heterojunction material, and perform mask plasma etching to form a lithiophilic patterned heterojunction array on its surface. Then, perform low-damage plasma etching to form a gradient porosity structure, obtaining a pretreated PET base film with a composite structure. Step 2: Mix copper sulfate, sulfuric acid, lanthanum nitrate, polyethylene glycol, modified polyether, and deionized water, stir at 30℃ for 25 min, and let stand for 22 h to obtain the electroplating solution. Step 3: Take the pretreated PET base film and immerse it in the electroplating solution. Electroplating is performed to form a copper layer. After electroplating, the material is rinsed and dried to obtain a functional current collector. In step 1, ultrasonic cleaning is performed using anhydrous ethanol, with the specific process conditions being: power 90W, time 4min; the drying process conditions are: temperature 55℃, time 25min. In step 1, the etched pattern of the plasma etching mask is circular with a diameter of 5μm and a pattern spacing of 2.5μm. In step 1, the ratio of the array area of the plasma etched mask to the surface area of the PET base film is 0.6:1. In step 1, the lithium-loving patterned heterogeneous... The spacing between adjacent heterojunctions in the heterojunction array is 0.5 times the lateral dimension of the etched pattern; in step 1, argon gas is used for low-damage plasma etching, with the specific process conditions being: power 180, time 25s, and argon flow rate 15sccm; the thickness of the surface void layer formed after etching is 0.4μm, and the porosity of the surface void layer is 40%; the thickness of the inner void layer formed after etching is 0.6μm, and the porosity of the inner void layer is 15%; the thickness of the PET base film after etching is 2.8μm; in step 2, the electroplating solution includes the following components by mass: copper sulfate 1 The electroplating solution contains 80 g / L sulfuric acid, 45 g / L sulfuric acid, 0.02 g / L lanthanum nitrate, 0.2 g / L polyethylene glycol, and 0.1 g / L modified polyether. In step 2, the modified polyether is obtained by mixing polyether sulfonate and polyether compound at a mass ratio of 1:2. The pH of the electroplating solution is 1. In step 3, electroplating is performed using a dual-pulse power supply, with the pretreated PET substrate film as the cathode and a titanium mesh as the anode, with a 6 cm distance between the electrodes. In step 3, the current density is gradually controlled during electroplating, as follows: The initial electroplating conditions are: forward current density 1.2 A / dm³. 2 Pulse width 35ms; reverse current density 0.3A / dm³ 2 The pulse width was 3ms, and the electroplating time was 4min. The process conditions during the middle stage of electroplating were: forward current density 1.8A / dm³. 2 Pulse width 30ms; reverse current density 0.4A / dm 2 The pulse width was 2ms, and the electroplating time was 7min. The post-electroplating process conditions were: forward current density 1.5A / dm³. 2 Pulse width 25ms; reverse current density 0.3A / dm³ 2The pulse width is 3ms, the electroplating time is 4min; the duty cycle of the electroplating process is 50%, the electroplating temperature is 40℃, the total electroplating time is 15min, and the thickness of the electroplated copper layer is 0.56μm; the thickness ratio of the surface void layer, inner void layer and electroplated copper layer of the PET base film is 1:1.5:1.4; in step 3, during the electroplating process, the electrolyte is circulated in a closed loop through a ceramic membrane circulation filtration system, and the specific process conditions are: filtration accuracy of 0.3μm and circulation flow rate of 8L / min; in step 3, deionized water is used for rinsing, and the rinsing pressure is 0.1MPa; in step 3, the drying process conditions are: temperature 45℃ and time 15min.
[0053] Example 7: When the polymer base film is a modified PP base film, a method for preparing a functional current collector based on a gradient pore structure includes the following processes: (1) Preparation of modified PP base film: PP resin, maleic anhydride-grafted PP, nano-SiO2, and antioxidant were mixed in a mass ratio of 92:4:3:0.4, and then melt-extruded using a twin-screw extruder and cast to obtain a 4.5 μm thick modified PP base film. The melt extrusion process conditions were: extrusion temperature 190℃, screw speed 200 r / min; the casting process conditions were: casting temperature 130℃, cooling roller temperature 45℃. (2) Preparation of functional current collectors: Step 1: Take a 4.5μm thick modified PP base film, clean and dry it, use zinc oxide as the heterojunction material, and perform mask plasma etching to form a lithiophilic patterned heterojunction array on its surface. Then, perform low-damage plasma etching to form a gradient pore structure, obtaining a pretreated modified PP base film with a composite structure. Step 2: Mix copper sulfate, sulfuric acid, lanthanum nitrate, polyethylene glycol, modified polyether, and deionized water, stir at 33℃ for 28 min, and let stand for 23 h to obtain the electroplating solution. Step 3: Take the pretreated modified PP base film and immerse it in the electroplating solution. Electroplating is performed to form a copper layer. After electroplating, the material is rinsed and dried to obtain a functional current collector. In step 1, ultrasonic cleaning is performed using anhydrous ethanol, with the specific process conditions being: power 95W, time 4.5min; the drying process conditions are: temperature 58℃, time 28min. In step 1, the etched pattern is circular with a diameter of 7μm and a pattern spacing of 4.0μm. In step 1, the ratio of the array area of the plasma etched mask to the surface area of the modified PP base film is 0.7:1. In step 1, the spacing between adjacent heterojunctions in the lithiophilic patterned heterojunction array is... The lateral dimension of the etched pattern is 0.6 times. In step 1, plasma low-damage etching is performed using a mixed gas of oxygen and argon at a volume ratio of 1:3. The specific process conditions are: power 220W, time 33s, and mixed gas flow rate 20sccm. The thickness of the surface void layer formed after etching is 0.6μm, and the porosity of the surface void layer is 43%. The thickness of the inner void layer formed after etching is 1.2μm, and the porosity of the inner void layer is 18%. The thickness of the modified PP base film after etching is 2.7μm. In step 2, the electroplating solution includes the following mass components: The electroplating solution contains 200 g / L copper sulfate, 50 g / L sulfuric acid, 0.03 g / L lanthanum nitrate, 0.3 g / L polyethylene glycol, and 0.2 g / L modified polyether. In step 2, the modified polyether is obtained by mixing polyether sulfonate and a polyether compound at a mass ratio of 1:2. The pH of the electroplating solution is 1. In step 3, electroplating is performed using a dual-pulse power supply, with the pretreated modified PP film as the cathode and a titanium mesh as the anode, with a 5 cm distance between the electrodes. In step 3, the current density is gradually controlled during electroplating, specifically as follows: the initial electroplating conditions are: forward current density 1.7 A / dm³. 2 Pulse width 43ms; reverse current density 0.4A / dm³ 2 The pulse width was 5ms, and the electroplating time was 5min. The process conditions during the middle stage of electroplating were: forward current density 2.2A / dm³. 2 Pulse width 33ms; reverse current density 0.6A / dm 2 The pulse width was 3ms, and the electroplating time was 7 minutes. The post-electroplating process conditions were: forward current density 1.9A / dm³. 2 Pulse width 28ms; reverse current density 0.4A / dm³ 2The pulse width was 5ms, the electroplating time was 7min; the duty cycle of the electroplating process was 50%, the electroplating temperature was 39℃, the total electroplating time was 19min, and the thickness of the electroplated copper layer was 1.2μm; the thickness ratio of the surface void layer, the inner void layer and the electroplated copper layer of the modified PP base film was 1:2.0:2.0; in step 3, during the electroplating process, the electrolyte was circulated in a closed loop through a ceramic membrane circulation filtration system, and the specific process conditions were: filtration accuracy of 0.5μm and circulation flow rate of 10L / min; in step 3, deionized water was used for rinsing, and the rinsing pressure was 0.1MPa; in step 3, the drying process conditions were: temperature 48℃ and time 18min.
[0054] Example 8: When the polymer base film is a modified PP base film, a method for preparing a functional current collector based on a gradient pore structure includes the following processes: (1) Preparation of modified PP base film: PP resin, maleic anhydride-grafted PP, nano-SiO2, and antioxidant were mixed in a mass ratio of 90:3:2:0.2, and then melt-extruded using a twin-screw extruder and cast to obtain a 4μm thick modified PP base film. The melt extrusion process conditions were: extrusion temperature 180℃, screw speed 180r / min; the casting process conditions were: casting temperature 120℃, cooling roller temperature 40℃. (2) Preparation of functional current collectors: Step 1: Take a 4μm thick modified PP base film, clean and dry it, use zinc oxide as the heterojunction material, and perform mask plasma etching to form a lithiophilic patterned heterojunction array on its surface. Then, perform low-damage plasma etching to form a gradient pore structure, obtaining a pretreated modified PP base film with a composite structure. Step 2: Mix copper sulfate, sulfuric acid, lanthanum nitrate, polyethylene glycol, modified polyether, and deionized water, stir at 30℃ for 25 min, and let stand for 22 h to obtain an electroplating solution. Step 3: Take the pretreated modified PP base film, immerse it in the electroplating solution, and perform... Electroplating is performed to form a copper layer. After electroplating, the material is rinsed and dried to obtain a functional current collector. In step 1, ultrasonic cleaning is performed using anhydrous ethanol under the following conditions: power 90W, time 4min. The drying conditions are: temperature 55℃, time 25min. In step 1, the etched pattern is circular with a diameter of 5μm and a pattern spacing of 2.5μm. In step 1, the ratio of the area of the plasma-etched array region of the mask to the surface area of the modified PP base film is 0.6:1. In step 1, the spacing between adjacent heterojunctions in the lithiophilic patterned heterojunction array is [etching distance missing]. The pattern's lateral dimension is 0.5 times; in step 1, a mixed gas of oxygen and argon at a volume ratio of 1:3 is used for low-damage plasma etching. Specific process conditions are: power 200W, time 30s, mixed gas flow rate 18sccm; the thickness of the surface void layer formed after etching is 0.5μm, and the porosity of the surface void layer is 40%; the thickness of the inner void layer formed after etching is 0.75μm, and the porosity of the inner void layer is 15%; the thickness of the modified PP base film after etching is 2.7μm; in step 2, the electroplating solution includes the following components by mass: sulfur The electroplating solution contains 180 g / L copper sulfate, 45 g / L sulfuric acid, 0.02 g / L lanthanum nitrate, 0.2 g / L polyethylene glycol, and 0.1 g / L modified polyether. In step 2, the modified polyether is obtained by mixing polyether sulfonate and a polyether compound at a mass ratio of 1:2. The pH of the electroplating solution is 1. In step 3, a dual-pulse power supply is used for electroplating, with the pretreated modified PP film as the cathode and a titanium mesh as the anode, with a 4 cm distance between the electrodes. In step 3, the current density is gradually controlled during electroplating, specifically as follows: the initial electroplating conditions are: forward current density 1.5 A / dm³. 2 Pulse width 40ms; reverse current density 0.4A / dm³ 2 The pulse width was 4ms, and the electroplating time was 5min. The process conditions during the middle stage of electroplating were: forward current density 2.0A / dm³. 2 Pulse width 30ms; reverse current density 0.5A / dm³ 2 The pulse width was 2ms, and the electroplating time was 7min. The post-electroplating process conditions were: forward current density 1.8A / dm³. 2 Pulse width 25ms; reverse current density 0.4A / dm³ 2The pulse width was 4ms, the electroplating time was 6min; the duty cycle of the electroplating process was 45%, the electroplating temperature was 38℃, the total electroplating time was 18min, and the thickness of the electroplated copper layer was 0.7μm; the thickness ratio of the surface void layer, the inner void layer and the electroplated copper layer of the modified PP base film was 1:1.5:1.4; in step 3, during the electroplating process, the electrolyte was circulated in a closed loop through a ceramic membrane circulation filtration system, and the specific process conditions were: filtration accuracy of 0.3μm and circulation flow rate of 8L / min; in step 3, deionized water was used for rinsing, and the rinsing pressure was 0.1MPa; in step 3, the drying process conditions were: temperature 45℃ and time 15min.
[0055] Example 9: When the polymer base film is a modified PP base film, a method for preparing a functional current collector based on a gradient pore structure includes the following processes: (1) Preparation of modified PP base film: S1: 3-Buten-1-ol, N,N-dimethylcyclohexylamine, and 1,4-dioxane were mixed and stirred until homogeneous. Then, 4-(2-epoxyethylene methoxy)benzoic acid was added. The mixture was heated under a nitrogen atmosphere. After the reaction was complete, it was cooled to 23°C, and NaOH was added. The mixture was stirred at 95 r / min for 25 min, filtered, and the filtrate was distilled to obtain a compound containing double bonds. S2: Polypropylene and xylene were mixed and heated to 115°C under a nitrogen atmosphere. The mixture was stirred until homogeneous, cooled to 80°C, and then… Benzoyl peroxide and a compound containing double bonds were added, and the reaction was carried out at a constant temperature. After the reaction was completed, acetone was added, and the mixture was stirred at 95 r / min for 35 min. After cooling, the filter cake was obtained, which is the high-temperature resistant polypropylene. S3: Under a nitrogen atmosphere, the high-temperature resistant polypropylene and xylene were mixed, heated to 70℃, stirred evenly, and then octadecanoyl chloride and triethylamine were added. The reaction was carried out at a constant temperature. After the reaction was completed, the mixture was cooled, filtered, dried, and ground to obtain modified polypropylene. S4: The modified polypropylene was melt-extruded, stretched into a film, and annealed to obtain modified P P-based film; In S1, the molar ratio of 3-buten-1-ol, N,N-dimethylcyclohexylamine, 1,4-dioxane, 4-(2-epoxyethylene methoxy)benzoic acid to NaOH is 1.3:0.04:25:1:0.7; In S1, the heating reaction conditions are: temperature 95℃, time 6h; In S1, the distillation conditions are: temperature 55℃, time 33min; In S2, the mass ratio of polypropylene, xylene, benzoyl peroxide, double-bonded compound, and acetone is 80:125:0. The process conditions for the isothermal reaction in S2 are: temperature 80℃, time 1.8h; the mass ratio of high-temperature resistant polypropylene, xylene, octadecyl chloride and triethylamine in S3 is 9:60:0.9:0.4; the process conditions for the isothermal reaction in S3 are: temperature 70℃, time 2.5h; the drying process conditions in S3 are: temperature 55℃, time 5h; the melt extrusion temperature in S4 is 245℃; the annealing process conditions in S4 are: temperature 115℃, time 65min. (2) Preparation of functional current collectors: Step 1: Take a 4.5μm thick modified PP base film, clean and dry it, use zinc oxide as the heterojunction material, and perform mask plasma etching to form a lithiophilic patterned heterojunction array on its surface. Then, perform low-damage plasma etching to form a gradient pore structure, obtaining a pretreated modified PP base film with a composite structure. Step 2: Mix copper sulfate, sulfuric acid, lanthanum nitrate, polyethylene glycol, modified polyether, and deionized water, stir at 33℃ for 28 min, and let stand for 23 h to obtain the electroplating solution. Step 3: Take the pretreated modified PP base film and immerse it in the electroplating solution. Electroplating is performed to form a copper layer. After electroplating, the material is rinsed and dried to obtain a functional current collector. In step 1, ultrasonic cleaning is performed using anhydrous ethanol, with the specific process conditions being: power 95W, time 4.5min; the drying process conditions are: temperature 58℃, time 28min. In step 1, the etched pattern is circular with a diameter of 7μm and a pattern spacing of 4.0μm. In step 1, the ratio of the array area of the plasma etched mask to the surface area of the modified PP base film is 0.7:1. In step 1, the spacing between adjacent heterojunctions in the lithiophilic patterned heterojunction array is... The lateral dimension of the etched pattern is 0.6 times. In step 1, plasma low-damage etching is performed using a mixed gas of oxygen and argon at a volume ratio of 1:3. The specific process conditions are: power 220W, time 33s, and mixed gas flow rate 20sccm. The thickness of the surface void layer formed after etching is 0.6μm, and the porosity of the surface void layer is 43%. The thickness of the inner void layer formed after etching is 1.2μm, and the porosity of the inner void layer is 18%. The thickness of the modified PP base film after etching is 2.7μm. In step 2, the electroplating solution includes the following mass components: The electroplating solution contains 200 g / L copper sulfate, 50 g / L sulfuric acid, 0.03 g / L lanthanum nitrate, 0.3 g / L polyethylene glycol, and 0.2 g / L modified polyether. In step 2, the modified polyether is obtained by mixing polyether sulfonate and a polyether compound at a mass ratio of 1:2. The pH of the electroplating solution is 1. In step 3, electroplating is performed using a dual-pulse power supply, with the pretreated modified PP film as the cathode and a titanium mesh as the anode, with a 5 cm distance between the electrodes. In step 3, the current density is gradually controlled during electroplating, specifically as follows: the initial electroplating conditions are: forward current density 1.7 A / dm³. 2 Pulse width 43ms; reverse current density 0.4A / dm³ 2 The pulse width was 5ms, and the electroplating time was 5min. The process conditions during the middle stage of electroplating were: forward current density 2.2A / dm³. 2 Pulse width 33ms; reverse current density 0.6A / dm 2 The pulse width was 3ms, and the electroplating time was 7 minutes. The post-electroplating process conditions were: forward current density 1.9A / dm³. 2 Pulse width 28ms; reverse current density 0.4A / dm³ 2The pulse width was 5ms, the electroplating time was 7min; the duty cycle of the electroplating process was 50%, the electroplating temperature was 39℃, the total electroplating time was 19min, and the thickness of the electroplated copper layer was 1.2μm; the thickness ratio of the surface void layer, the inner void layer and the electroplated copper layer of the modified PP base film was 1:2.0:2.0; in step 3, during the electroplating process, the electrolyte was circulated in a closed loop through a ceramic membrane circulation filtration system, and the specific process conditions were: filtration accuracy of 0.5μm and circulation flow rate of 10L / min; in step 3, deionized water was used for rinsing, and the rinsing pressure was 0.1MPa; in step 3, the drying process conditions were: temperature 48℃ and time 18min.
[0056] Example 10: When the polymer base membrane is a modified PP base membrane, a method for preparing a functional current collector based on a gradient pore structure includes the following processes: (1) Preparation of modified PP base film: S1: 3-Buten-1-ol, N,N-dimethylcyclohexylamine, and 1,4-dioxane were mixed and stirred until homogeneous. Then, 4-(2-epoxyethylene methoxy)benzoic acid was added. The mixture was heated under a nitrogen atmosphere. After the reaction was complete, it was cooled to 20°C, and NaOH was added. The mixture was stirred at 90 r / min for 20 min, filtered, and the filtrate was distilled to obtain a compound containing double bonds. S2: Polypropylene and xylene were mixed and heated to 110°C under a nitrogen atmosphere. The mixture was stirred until homogeneous, cooled to 75°C, and then… Benzoyl peroxide and a compound containing double bonds were added, and the reaction was carried out at a constant temperature. After the reaction was completed, acetone was added, and the mixture was stirred at 90 r / min for 30 min. After cooling, the filter cake was obtained, which is the high-temperature resistant polypropylene. S3: Under a nitrogen atmosphere, the high-temperature resistant polypropylene and xylene were mixed, heated to 60℃, stirred evenly, and then octadecanoyl chloride and triethylamine were added. The reaction was carried out at a constant temperature. After the reaction was completed, the mixture was cooled, filtered, dried, and ground to obtain modified polypropylene. S4: The modified polypropylene was melt-extruded, stretched into a film, and annealed to obtain modified polypropylene. PP base film; In S1, the molar ratio of 3-buten-1-ol, N,N-dimethylcyclohexylamine, 1,4-dioxane, 4-(2-epoxyethylene methoxy)benzoic acid to NaOH is 1.0:0.03:20:1:0.6; In S1, the heating reaction conditions are: temperature 90℃, time 5h; In S1, the distillation conditions are: temperature 50℃, time 30min; In S2, the mass ratio of polypropylene, xylene, benzoyl peroxide, double-bonded compound, and acetone is 70:100. The ratio of polypropylene, xylene, octadecyl chloride, and triethylamine in S2 is 0.4:8:100; the isothermal reaction conditions in S3 are: temperature 75℃, time 1.5h; the isothermal reaction conditions in S3 are: temperature 60℃, time 2h; the drying conditions in S3 are: temperature 50℃, time 4h; the melt extrusion temperature in S4 is 240℃; the annealing conditions in S4 are: temperature 110℃, time 60min. (2) Preparation of functional current collectors: Step 1: Take a 4μm thick modified PP base film, clean and dry it, use zinc oxide as the heterojunction material, and perform mask plasma etching to form a lithiophilic patterned heterojunction array on its surface. Then, perform low-damage plasma etching to form a gradient pore structure, obtaining a pretreated modified PP base film with a composite structure. Step 2: Mix copper sulfate, sulfuric acid, lanthanum nitrate, polyethylene glycol, modified polyether, and deionized water, stir at 30℃ for 25 min, and let stand for 22 h to obtain an electroplating solution. Step 3: Take the pretreated modified PP base film, immerse it in the electroplating solution, and perform... Electroplating is performed to form a copper layer. After electroplating, the material is rinsed and dried to obtain a functional current collector. In step 1, ultrasonic cleaning is performed using anhydrous ethanol under the following conditions: power 90W, time 4min. The drying conditions are: temperature 55℃, time 25min. In step 1, the etched pattern is circular with a diameter of 5μm and a pattern spacing of 2.5μm. In step 1, the ratio of the area of the plasma-etched array region of the mask to the surface area of the modified PP base film is 0.6:1. In step 1, the spacing between adjacent heterojunctions in the lithiophilic patterned heterojunction array is [etching distance missing]. The pattern's lateral dimension is 0.5 times; in step 1, a mixed gas of oxygen and argon at a volume ratio of 1:3 is used for low-damage plasma etching. Specific process conditions are: power 200W, time 30s, mixed gas flow rate 18sccm; the thickness of the surface void layer formed after etching is 0.5μm, and the porosity of the surface void layer is 40%; the thickness of the inner void layer formed after etching is 0.75μm, and the porosity of the inner void layer is 15%; the thickness of the modified PP base film after etching is 2.7μm; in step 2, the electroplating solution includes the following components by mass: sulfur The electroplating solution contains 180 g / L copper sulfate, 45 g / L sulfuric acid, 0.02 g / L lanthanum nitrate, 0.2 g / L polyethylene glycol, and 0.1 g / L modified polyether. In step 2, the modified polyether is obtained by mixing polyether sulfonate and a polyether compound at a mass ratio of 1:2. The pH of the electroplating solution is 1. In step 3, a dual-pulse power supply is used for electroplating, with the pretreated modified PP film as the cathode and a titanium mesh as the anode, with a 4 cm distance between the electrodes. In step 3, the current density is gradually controlled during electroplating, specifically as follows: the initial electroplating conditions are: forward current density 1.5 A / dm³. 2 Pulse width 40ms; reverse current density 0.4A / dm³ 2 The pulse width was 4ms, and the electroplating time was 5min. The process conditions during the middle stage of electroplating were: forward current density 2.0A / dm³. 2 Pulse width 30ms; reverse current density 0.5A / dm³ 2 The pulse width was 2ms, and the electroplating time was 7min. The post-electroplating process conditions were: forward current density 1.8A / dm³. 2 Pulse width 25ms; reverse current density 0.4A / dm³ 2The pulse width was 4ms, the electroplating time was 6min; the duty cycle of the electroplating process was 45%, the electroplating temperature was 38℃, the total electroplating time was 18min, and the thickness of the electroplated copper layer was 0.7μm; the thickness ratio of the surface void layer, the inner void layer and the electroplated copper layer of the modified PP base film was 1:1.5:1.4; in step 3, during the electroplating process, the electrolyte was circulated in a closed loop through a ceramic membrane circulation filtration system, and the specific process conditions were: filtration accuracy of 0.3μm and circulation flow rate of 8L / min; in step 3, deionized water was used for rinsing, and the rinsing pressure was 0.1MPa; in step 3, the drying process conditions were: temperature 45℃ and time 15min.
[0057] Comparative Example 1: Compared with Example 1, the PET substrate film was directly subjected to low-damage plasma etching to form a surface void layer with a porosity of 45% and a thickness of 0.5 μm, without an inner void layer. No mask-mounted argon plasma etching was performed, and no modified polyether was added to the electroplating solution. A fixed forward 1.8 A / dm was used. 2 Electroplating was performed using a pulse process for 18 minutes, with all other conditions being the same as in Example 1.
[0058] Comparative Example 2: Compared with Example 1, only the argon plasma etching of the mask was omitted, and all other conditions were the same as in Example 1.
[0059] Comparative Example 3: Compared with Example 1, no modified polyether was added to the electroplating solution, and all other conditions were the same as in Example 1.
[0060] Comparative Example 4: Compared with Example 1, the stepped electroplating process was adjusted to a fixed positive current density of 1.8 A / dm³. 2 Reverse current density 0.4 A / dm 2 The pulse process was used, and all other conditions were the same as in Example 1.
[0061] Comparative Example 5: Compared with Example 2, high-temperature resistant polypropylene was directly melt-extruded, stretched into a film, and a modified PP base film was formed. All other conditions remained unchanged and were the same as in Example 2.
[0062] Comparative Example 6: Compared with Example 2, the modified PP base film was replaced with a PP base film, and the other conditions remained the same as in Example 2.
[0063] Experiment: The functional current collectors obtained in the examples and comparative examples were used to make pouch cells, and the performance of the functional current collectors and pouch cells was tested. Fabrication of pouch cells: Step A: Mix NCM811, PVDF, and conductive carbon black at a mass ratio of 96:2:2, stir uniformly to obtain a positive electrode slurry, coat the positive electrode slurry on the upper and lower surfaces of an 8 μm thick aluminum foil, and dry to obtain a positive electrode sheet; Step B: Mix artificial graphite, CMC, SBR, and conductive carbon black at a mass ratio of 95:2:2:1, stir uniformly to obtain a negative electrode slurry, coat the negative electrode slurry on the upper and lower surfaces of a functional current collector, and dry to obtain a negative electrode sheet; Step C: Subject the positive electrode sheet and the negative electrode sheet to rolling, slitting, and die-cutting, then stack them with a 12 μm thick acrylonitrile separator in the order of "positive electrode sheet - separator - negative electrode sheet - separator", perform assembly, electrolyte injection, formation, and capacity grading to obtain a pouch battery; the coating thickness of the positive electrode slurry in Step A is 80 μm; the coating thickness of the negative electrode slurry in Step B is 80 μm; in Step A and Step B, the drying process conditions are: a temperature of 120°C and a duration of 2.5 h; in Step C, the electrolyte comprises the following components, by mass percentage: 16% LiPF6, 24% DEC, 32% EC, 24% EMC, 2.4% VC, and 1.6% PS; Mechanical property test: Refer to GB / T 1040.1-2025 to test the tensile strength of the prepared functional current collector, so as to characterize its mechanical properties; Processing bending test: According to the GB / T 15254-2018 standard, cut the composite current collector into a 100 mm × 20 mm test specimen, use a bending tester, set the bending angle to 180°, the bending speed to 10 times / min, and the bending radius equal to the total thickness of the current collector, perform continuous bending, and record the number of bending cycles when cracks, coating peeling or base film fracture occurs on the test specimen; the judgment criterion is that 10 bending cycles without cracks or peeling is qualified; Adhesion test: Refer to ASTM D3359 to test the adhesion of the copper plating layer on the surface of the prepared functional current collector; Thickness deviation test: Use a high-precision thickness gauge with an accuracy of 0.01 μm, select 10 uniformly distributed test points (with a spacing ≥ 10 mm) randomly on the surface of the test specimen, measure the total thickness of the current collector and the thickness of the copper plating layer respectively, and calculate the average thickness of the 10 test points; thickness deviation = (thickness of a single test point - average value) / average value × 100%, and the maximum deviation value is taken as the final result; Electrolyte utilization test: Adopt the gravimetric method, record the mass of the electrolyte before and after electroplating (accurate to 0.001 g) and the mass of the electrolyte supplemented during the electroplating process; electrolyte utilization rate = (mass of electrolyte consumed by electroplating / (initial electrolyte mass + supplemented electrolyte mass)) × 100%; where the mass of electrolyte consumed by electroplating = initial electrolyte mass + supplemented electrolyte mass - electrolyte mass after completion; Lithium-ion deposition uniformity test: The surface and cross-section of the composite current collector coating were observed using a scanning electron microscope (SEM) (magnification 5000x). Three different fields of view were selected, and the proportion of lithium-ion deposition area in each field of view was statistically analyzed using image analysis software. The coefficient of variation of the three fields of view was calculated (coefficient of variation = (standard deviation / mean) × 100%). The smaller the coefficient of variation, the more uniform the deposition. ≤5% is considered uniform. Electrolyte wetting rate test: Using the capillary rise method, the composite current collector was cut into 20mm×50mm samples and vertically inserted into the lithium-ion battery electrolyte (insertion depth 5mm). The time required for the electrolyte to rise 10mm on the sample surface was recorded. Wetting rate = 10mm / time required (unit: mm / min). The higher the rate, the better the wetting. Cycle capacity retention test: The soft-pack battery was charged and discharged using a charge-discharge tester with a voltage range of 2.8~4.2V and a discharge current of 3C. The cycle capacity retention was tested after 500 cycles. Pore filling rate test: The cross-section of the composite current collector was observed using SEM (magnified 10,000 times). Five different pore regions were selected, and the actual filling area of each pore and the total pore area were measured using image analysis software. Pore filling rate = (actual filling area / total pore area) × 100%. The average value of the five regions was taken as the final result. Plating solution stability maintenance time test: The prepared electrolyte was placed in a constant temperature environment of 35℃ (without stirring), and samples were taken every 12 hours. The concentrations of copper sulfate, lanthanum nitrate, polyethylene glycol, and modified polyether in the electrolyte were detected by CVS. When the concentration deviation of any component exceeded 5% of the initial concentration, the time from the completion of preparation to this point was recorded, which is the plating solution stability maintenance time. Coating grain size testing: The XRD pattern of the coating was measured using an X-ray diffractometer (XRD). The grain size was calculated according to the Scherrer formula D=Kλ / (βcosθ), where D is the grain size (nm), K=0.89 (Scherrer constant), λ=0.154nm (X-ray wavelength), β is the full width at half maximum (FWHM) of the diffraction peak (rad), and θ is the diffraction angle (°). Three characteristic diffraction peaks were selected, and the average value was calculated as the coating grain size.
[0064]
[0065] Based on the information in the table above, the following conclusions can be drawn: Compared to Example 1, Comparative Example 1 directly performed low-damage plasma etching on the PET substrate film without mask argon plasma etching, and did not add modified polyether to the electroplating solution, using a fixed forward flux of 1.8 A / dm. 2When electroplating is performed using a pulse process, the performance of the functional current collector deteriorates to varying degrees, and the performance of the resulting pouch cell also decreases. Compared to Example 1, Comparative Example 2 only eliminated the argon plasma etching of the mask, resulting in a decrease in the uniformity of lithium-ion deposition; Compared with Example 1, Comparative Example 3 did not add modified polyether to the electroplating solution, and the stability maintenance time of the plating solution and the grain size of the coating were both deteriorated. Compared with Example 1, Comparative Example 4 changed the step-by-step electroplating process to a fixed positive pulse process, which reduced the pore filling rate of the functional current collector. Compared with Example 2, Comparative Example 5 directly melt-extruded high-temperature resistant polypropylene, stretched it into a film, and formed a modified PP base film, which showed a more significant decrease in functionality and fluid mechanical properties. Compared with Example 2, in Comparative Example 6, the modified PP base film was replaced with a PP base film, and the performance of the functional current collector deteriorated to varying degrees, and the performance of the prepared soft-pack battery also decreased. In summary, the synergistic effect of the "patterned heterojunction" and "gradient porosity" in this application, the synergistic effect of the modified polyether introduced into the copper plating solution with lanthanum nitrate and polyethylene glycol, the use of a current density gradient control process, and the introduction of thermally stable benzoic acid groups and tough long carbon chains into the polypropylene molecular chain can comprehensively improve the overall performance of the manufactured functional current collector and pouch battery.
[0066] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A method for preparing a functional current collector based on a gradient pore structure, characterized in that: Including the following processes: Step 1: Take a polymer base film, clean it, dry it and perform mask plasma etching to form a lithiophilic patterned heterojunction array on its surface, and then perform low-damage plasma etching to form a gradient pore structure, thus obtaining a pretreated polymer base film with a composite structure. Step 2: Mix copper sulfate, sulfuric acid, lanthanum nitrate, polyethylene glycol, modified polyether and deionized water, stir at 30~35℃ for 25~30 min, let stand for 22~24 h to obtain electroplating solution; Step 3: Take the pretreated polymer base film, put it into the electroplating solution, and electroplat it to form an electroplated copper layer. After the electroplating is completed, rinse and dry it to obtain the functional current collector. In step 1, the polymer base film is either a PET base film or a modified PP base film.
2. The method for preparing a functional current collector based on a gradient pore structure according to claim 1, characterized in that: In step 1, the process conditions for plasma etching of the mask are as follows: zinc oxide is used as the heterojunction material, the etched pattern is circular with a diameter of 5~8μm and a pattern spacing of 2.5~6.4μm.
3. The method for preparing a functional current collector based on a gradient pore structure according to claim 1, characterized in that: In step 2, the electroplating solution comprises the following components by mass: copper sulfate 180~220g / L, sulfuric acid 45~55g / L, lanthanum nitrate 0.02~0.05g / L, polyethylene glycol 0.2~0.4g / L, and modified polyether 0.1~0.3g / L.
4. The method for preparing a functional current collector based on a gradient pore structure according to claim 3, characterized in that: In step 2, the modified polyether is obtained by mixing polyether sulfonate and polyether compound at a mass ratio of 1:
2.
5. The method for preparing a functional current collector based on a gradient pore structure according to claim 1, characterized in that: In step 3, a dual-pulse power supply is used for electroplating, with the pretreated polymer base film as the cathode and the titanium mesh as the anode, and the distance between the two electrodes is 4~6cm.
6. The method for preparing a functional current collector based on a gradient pore structure according to claim 1, characterized in that: In step 3, when the polymer base film is a PET base film, the electroplating process conditions are as follows; The initial process conditions for electroplating are: forward current density 1.2~1.5A / dm³. 2 Pulse width 35~40ms; reverse current density 0.3~0.4A / dm³ 2 Pulse width 3~5ms, electroplating time 4~5min; The process conditions during the intermediate stage of electroplating are: forward current density 1.8~2.2 A / dm³. 2 Pulse width 30~35ms; reverse current density 0.4~0.6A / dm³ 2 Pulse width 2~4ms, electroplating time 7~8min; The post-electroplating process conditions are: forward current density 1.5~1.8 A / dm³. 2 Pulse width 25~30ms; reverse current density 0.3~0.4A / dm³ 2 Pulse width 3~5ms, electroplating time 4~5min; The electroplating process has a duty cycle of 50-60%, an electroplating temperature of 40-42℃, a total electroplating time of 15-18 minutes, and a copper layer thickness of 0.56-1.5μm.
7. The method for preparing a functional current collector based on a gradient pore structure according to claim 1, characterized in that: In step 3, when the polymer base film is a modified PP base film, the electroplating process conditions are as follows; The initial process conditions for electroplating are: forward current density 1.5~1.8 A / dm³. 2 Pulse width 40~45ms; reverse current density 0.4~0.5A / dm³ 2 Pulse width 4~6ms, electroplating time 5~6min; The process conditions during the intermediate stage of electroplating are: forward current density 2.0~2.4A / dm³. 2 Pulse width 30~35ms; reverse current density 0.5~0.7A / dm³ 2 Pulse width 2~4ms, electroplating time 7~8min; The post-electroplating process conditions are: forward current density 1.8~2.0 A / dm³. 2 Pulse width 25~30ms; reverse current density 0.4~0.5A / dm³ 2 Pulse width 4~6ms, electroplating time 6~7min; The electroplating process has a duty cycle of 45-55%, an electroplating temperature of 38-40℃, a total electroplating time of 18-21 min, and a copper layer thickness of 0.7-1.75 μm.
8. The method for preparing a functional current collector based on a gradient pore structure according to claim 1, characterized in that: The modified PP base film is prepared by the following process: PP resin, maleic anhydride-grafted PP, nano-SiO2, and antioxidant are mixed, melt-extruded through a twin-screw extruder, and cast to obtain a modified PP base film.
9. The method for preparing a functional current collector based on a gradient pore structure according to claim 1, characterized in that: The modified PP base film can also be obtained by the following process: S1: Mix 3-buten-1-ol, N,N-dimethylcyclohexylamine, and 1,4-dioxane, stir until homogeneous, then add 4-(2-epoxyethylene methoxy)benzoic acid. Under a nitrogen atmosphere, heat the mixture to react. After the reaction is complete, cool to 20-25°C, add NaOH, and stir at 90-100 r / min for 20-30 min. Filter the mixture and distill the filtrate to obtain a compound containing double bonds. S2: Mix polypropylene and xylene, heat to 110~120℃ under nitrogen atmosphere, stir evenly, cool to 75~85℃, then add benzoyl peroxide and compounds containing double bonds, react at constant temperature, add acetone after the reaction is complete, stir at 90~100r / min for 30~40min, cool, filter to obtain filter cake, which is high temperature resistant polypropylene; S3: Under nitrogen atmosphere protection, high temperature resistant polypropylene and xylene are mixed, heated to 60~80℃, stirred evenly, then octadecanoyl chloride and triethylamine are added, and the reaction is carried out at a constant temperature. After the reaction is completed, the mixture is cooled, filtered, dried and ground to obtain modified polypropylene. S4: Modified polypropylene is melt-extruded, stretched into a film, and annealed to obtain a modified PP base film.
10. A functional current collector based on a gradient pore structure, characterized in that: The preparation method according to any one of claims 1 to 9 is used.
Citation Information
Patent Citations
Compounding brightener for copper plating and preparation method thereof
CN107177868A